Dimensões de proximidades em ecossistemas regionais de inovação emergentes: elementos para compreender seu funcionamento - Silva, Jackson Dener Serafim (Universidade do Vale do Rio dos Sinos, 2024)
The objective of this study is to analyze the configurations of proximity dimensions among actors operating within the Regional Innovation Ecosystem (ERI) of the Vales region in Rio Grande do Sul, based on the innovation support programs of the Secretariat of Innovation, Science, and Technology of Rio Grande do Sul (SICT/RS). The research is grounded in the theoretical approach of proximity dimensions (geographic, cognitive, organizational, social, and institutional), as proposed by Boschma (2005), aiming to identify how these dimensions influence the dynamics of collaboration among ecosystem actors, while also considering potential barriers and lock-in effects that may arise throughout the process. The research problem guiding this work is as follows: how do the configurations of proximity dimensions contribute to understanding the functioning of an emerging innovation ecosystem? To answer this question, a qualitative methodology was adopted, based on content analysis of innovation projects funded by SICT/RS programs between 2020 and 2023. Data collection included the analysis of official project documents and in-depth interviews with coordinators of five projects. The triangulation of these sources enabled a detailed analysis of interactions among the key actors in the ERI of the Vales region. The results revealed that the proximity dimensions play distinct roles in building collaboration networks. Organizational proximity is driven by previous interinstitutional relationships, facilitating the integration of new projects and partners. However, cognitive proximity stands out as a crucial factor, as the technical qualification of the actors involved is essential for executing the more complex activities of the projects. This dimension also poses a barrier, as the difficulty in attracting and retaining qualified researchers, due to the low value of research grants, was a recurring issue. Social proximity, based on prior collaborations and trust ties, also proved to be a cohesive factor but simultaneously demonstrated the potential to create a lock-in effect, limiting the inclusion of new partners in the ecosystem. Institutional proximity was evident, as the rules and budgetary requirements imposed by SICT/RS created significant barriers, such as delays in purchasing equipment and reagents, hindering the fulfillment of project timelines. The interviews also revealed that municipal governments, as institutional partners, often struggle to align their bureaucratic processes with the innovative demands of the projects, posing additional challenges for carrying out planned activities. The discussion highlighted that, although the proximity dimensions are essential for the functioning of the ERI of the Vales, the barriers related to institutional and cognitive proximity represent obstacles that may compromise the ecosystem's sustainability in the long term. Greater flexibility in innovation policies, combined with a higher valuation of the human resources involved in the projects, could mitigate these challenges, promoting the development of a more dynamic and inclusive ecosystem. It is concluded that, for the ERI of the Vales to reach greater maturity, a coordinated effort among ecosystem actors is necessary to overcome the identified barriers, particularly regarding institutional and cognitive proximity. The inclusion of new mechanisms for trust-building and incentives for innovation within municipal governments and other local entities could expand the diversity of partnerships and strengthen the ecosystem, making it more resilient and better prepared to face innovation challenges in the regional context.
Keywords: Ecossistemas de inovação; Dimensões de proximidade; Estudo de caso; Boschma (2005); Innovation ecosystems; Proximity dimensions; Case study; ACCNPQ::Ciências Sociais Aplicadas::Administração